POSSIBILITIES OF APPLICATION OF CRIME PREVENTION THROUGH ENVIRONMENTAL DESIGN (CPTED) IN LITHUANIAN COMMERCIAL OBJECTS - Matijosaitiene, Irina; Dambriunas, Maria (European Scientific Journal, ESJ, 2015)
Five commercial objects (Soviet-time, fully reconstructed and newly built) located on one of the most crime-ridden and problematic streets of Kaunas city, Lithuania, are researched according to crime prevention through environmental design (CPTED) strategies: natural surveillance, access control, territoriality, maintenance, and activity support. Theft from motor vehicle, robbery and intentional damage of property are analyzed. Research results reveal that CPTED is poorly implemented in all analyzed objects. Though, in Soviet-time commercial objects it is even harder to implement activity support strategy. Correlation analysis demonstrates significant strong relations between the analyzed crimes and some criteria from surveillance, access control, territoriality and activity support strategies. Recommendations for safety improvement in commercial objects are proposed based on CPTED strategies.